Therapeutic Applications of Low-intensity Pulsed Ultrasound in Osteoporosis - Rashidi, Samaneh (Asian Journal of Pharmaceutics (AJP), 2017)
Ultrasound (US) waves due to their unique features can be a treatment option for osteoporosis. Initial studies have shown promising but controversial outcomes. Several preclinical and clinical studies have been conducted on osteoporosis and studies are ongoing to find optimum US parameters, mechanisms of action, and therapeutic efficacies of these techniques for osteoporosis treatment. This paper was aimed to review the recent advances of using US waves in the treatment of osteoporosis and possible mechanisms of actions. The databases of PubMed (1980-2016), EMBASE (1980-2016), Web of Sciences (1980-2016), and Google Scholar (1980-2016) were searched using the set terms. The obtained records were reviewed, and relevant studies were selected for comprehensive review of the current literature. Low-intensity pulsed US (LIPUS) has biological effects on the bone healing process and it can accelerate bone regeneration. Current evidence is limited on the efficacy of US waves for treatment or prevention of osteoporosis; however, the initial studies are promising. The US waves can promote osteoblast and inhibit osteoclast, enhance angiogenesis, trigger expression of different genes associated with osteogenesis. No definite dose-response existed on the clinical trials of US wave applications. The current evidence shows the therapeutic efficacy of US waves particularly LIPUS for osteoporosis treatment; however, to observe therapeutic outcomes long-term US stimulation is required. No definitive dose-response is proposed for osteoporosis. Further in vitro and clinical trials should be conducted to develop US-based techniques for the treatment of osteoporosis as a clinical treatment option.